Efficiency of Сognitive Behavioral Training as a Means of Reducing Verbal Manifestations of Anxiety Under Emotional Stress - Turchak, Olesia (East European Journal of Psycholinguistics, 2015)
As the aim of the research the author defines the analysis of the efficacy of cognitive-behavioral training as a mean of reducing verbal manifestations of anxiety in situations of emotional stress. In accordance with the intended aim, the article presents the results of testing of cognitive-behavioral training for the formation of control over verbal manifestations of students’ anxiety in situations of emotional stress. In this study they participated 40 first-year students of natural specialties. Both experimental and control group consisted of 20 people (10 boys and 10 girls in each). As a result, it was found that the cognitive-behavioral training helped to reduce the level of speech anxiety (t = 6.3; n = 20, p≤0.05), situational anxiety (t = 3.7; n = 20, p≤ 0.05) and trait anxiety (t = 7.1; n = 20, p≤0.05) of students in the experimental group. Furthermore, the students in the experimental group showed significant reduction in emotional lability (t = 5, n = 20, p≤0.05), as well as increased introversion (t = 2.1; n = 20, p≤ 0.05). The findings suggest that the training contributes to the development of self-regulation skills of students, who have developed resistance to emotional stress situations, and also forms the willingness to communicate with other people. This suggests that cognitive-behavioral training is an effective means of reducing verbal manifestations of anxiety in situations of emotional stress. References Bohonkova, Yu. (2005) Osobystisni Сhynnyky Sotsialno-Psyhologichnoi Adaptatsi Pershokursnykiv do Umov Vyschyh Navchalnyh Zakladiv [Personality Factors of Social and Psychological Adjustment of Freshmen to the Terms of Higher Education Institutions]. Luhansk. Izard, K. (1999). Psihologiia Emotsii [Psychology of Emotions]. St. Petersburg: Piter. Korobko, O. (2010). Stan emotsiinoi naprugy u navchalnomu protsesi ta kognityvnopovedinkovi zasoby iogo podolannia [Emotional anxiety in educational process and cognitivebehavioral means of its overcoming]. Naukovi Zapysky, 14, 177–185. Ostroh: Ostrozka Akademiia. Korsini, R. (2003). Psihologicheskaia Entsiklopedia [Psychological Encyclopedia]. St. Petersburg: Piter. Krylov, A. (2007). Praktikum po Obschei, Eksperimentalnoi i Prikladnoi Psihologii [Manual on General, Experimental and Applied Psychology]. St. Petersburg: Piter. Leontyev, A. (1997). Osnovy Psiholingvistiki [Foundations of Psycholinguistics]. Moscow. Turchak, O. (2014). Treningova programa ormuvannia kontroliu za kharakterystykamy movlennia studentiv u sytuatsiiah emotsiinoi naprugy [Training Program to Establish Control over the Characteristics of Students’ Speech in Situations of Emotional Stress]. Kyiv: Komprynt.